Nexus between electricity generation and economic growth in Malaysia / Haeruddin Mohd Noor - Mohd Noor, Haeruddin (2013)
This study work on Nexus between electricity generation and economic growth in Malaysia data covering the period 1978-2011 and run Granger-causality test that used by A.R. Sarker (2010) who found the existing unidirectional causal relationship between electricity generation and economic growth in Bangladesh. The results conclude that changes in electricity generation have significance contribution in the change in economic growth. This paper recommend policy and alternative to enhance the electricity generation as well as to enhance the economic growth in Malaysia.